Prevalence of Antibiotic Resistance among Escherichia coli from Different Sources in Malaysia - Alhaj, N.; Mariana, N.S.; Raha, A.R.; Ishak, Z. (International Journal of Poultry Science, 2007)
Antimicrobial agent resistance has been recognized as an emerging worldwide problem in both human and animals, antimicrobial agent use is considered the most important factor for the emergence, selection and dissemination of antimicrobial agent-resistant bacteria, intrinsically either acquires the resistance gene from other bacterial environment or development of pumping out mechanism. The aim of this study was to generate baseline data on the prevalence of antimicrobial resistance in Escherichia coli isolates from different sources. Seventy E. coli isolates from humans and environments were tested for susceptibility to 10 antimicrobial agents by diffusion method. Resistance was found in 61.2% of the isolates. The most prevalent resistances were to kanamycin and tetracycline (81.4%), followed by chloramphenicol (75.7%) and gentamicin, (74.3%). The low prevalent were to cefetoxin (44.3%), norofluoxacin (27.1%) and ciprofluoxacin (24.3%). This study showed the distribution of antimicrobial agent resistance in E. coli isolates from a variety of sources and analysis of such patterns of resistance may prove to be useful beyond simple description. Regarding to the concern of water quality and environmental contamination by human and agricultural waster have increased, it has become increasingly important to develop low-cost screening tools that can be used to identify the most probable source of contamination.